PEREMPUAN PENCARI NAFKAH UTAMA Studi Analisis Fenomenologi Di Kota Subulussalam - fasya, fasya (IAIN Langsa, 2018)
The research was aimed to find out the role of women as the main breadwinner in Subulussalam. This research used a field-research with a phenomenology approach with a descriptive qualitative -inductive research. The subjects of this study were the women as breadwinners in Subulussalam. The results of this research indicate that the women in Subulussalam very have a role for her familyas the main breadwinner. It effected due to the low income of her husband, the high level of the necessities of life, the number of the cost of her children's life and their education, the existence of encouragement from within in order to obtain a better life are well established, and the existence of women's desire to work.A women generally choose a job in the informal sector, such as selling, selling cakes around, selling herbs around, scavenged, domestic workers, farm laborers, garden laborers, and other work. The reasons for choosing such occupations are the difficulty of getting a job, lack of employment, lack of women's creativity, lack of skills, and the absence of the capital to open their own business. The constraints faced are the lack of business capital, the number of rivals in work and the absence of transportation. The dual role of women as a housewife and as the main breadwinner for her family have an effect on not maximal the woman in running both function. The government's efforts in the welfare of women's economy are to socialize policies, empower women programs, provide guidance to women, assistance in solving women's problems and provide business capital assistance.